The role of tetrahydrobiopterin in inflammation and cardiovascular disease - McNeill, Eileen; Channon, Keith M. (Thrombosis and Haemostasis, 2012)
The cofactor tetrahydrobiopterin (BH4) is required for nitric oxide (NO) production by all nitric oxide synthase (NOS) enzymes and is a key regulator of cellular redox signalling. When BH4 levels become limiting NOS enzymes become ‘uncoupled’ and produce superoxide rather than NO. Endothelial cell BH4 is required for the maintenance of vascular function through NO production, and reduced BH4 levels are associated with vascular dysfunction. Evidence increasingly points to important roles for BH4 and NOS enzymes in other vascular cell types. Leukocytes have a fundamental role in atherosclerosis, and new evidence points to a role in the control of hypertension. Leukocytes are a major site of iNOS expression, and the regulation of this isoform is another mechanism by which BH4 availability may modulate disease. This review provides an overview of BH4 control of NOS function in both endothelial cells and leukocytes in the context of vascular disease and current therapeutic evaluations.
Keywords: Tetrahydrobiopterin; BH4; vascular disease; reactive oxygen species (ROS); nitric oxide